2021
DOI: 10.1177/00405175211026537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental temperature and humidity on evaporative heat loss through firefighter suit materials made with semi-permeable and microporous moisture barriers

Abstract: The goal of this research was to understand how firefighter protective suits perform in different operational environments. This study used a sweating guarded hotplate to examine the effect of environmental temperature (20–45°C) and relative humidity (25–85% RH) on evaporative heat loss through firefighter turnout materials. Four firefighter turnout composites containing three different bi-component (semi-permeable) and one microporous moisture barriers were selected. The results showed that the evaporative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 30 publications
(28 reference statements)
2
24
0
Order By: Relevance
“…When tested in standard nonisothermal ambient conditions of temperature and humidity without incident solar radiation, turnout composites gained weight because of moisture condensation. 6 We also found that under no radiation, the moisture content inside the moisture barriers and thermal liners was similar, but higher than that of the outer shells (p < 0.05). A similar phenomenon was reported by He et al 42 A possible reason for the higher water absorption in the thermal liner is that the thermal liner was closer to the water-saturated hotplate surface, which would have resulted in a more humid microenvironment.…”
Section: Effects Of Outer Shell Fabric Color and Texture On Heat Loss...supporting
confidence: 59%
See 3 more Smart Citations
“…When tested in standard nonisothermal ambient conditions of temperature and humidity without incident solar radiation, turnout composites gained weight because of moisture condensation. 6 We also found that under no radiation, the moisture content inside the moisture barriers and thermal liners was similar, but higher than that of the outer shells (p < 0.05). A similar phenomenon was reported by He et al 42 A possible reason for the higher water absorption in the thermal liner is that the thermal liner was closer to the water-saturated hotplate surface, which would have resulted in a more humid microenvironment.…”
Section: Effects Of Outer Shell Fabric Color and Texture On Heat Loss...supporting
confidence: 59%
“…The drying effect caused by radiation would decrease the performance of turnout systems with bi-component moisture barriers. 6…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These films are not porous and are hence water impermeable 1,5 . In this latter scenario, the breathability is attributed to the molecular absorption‐diffusion‐desorption mechanism, which in turn is driven by the temperature and humidity gradient 6–8 . Hydrophilic polymers generally possess polar groups such as hydroxyl (OH), amino (NH 2 ), carboxyl (COOH), or ether (O) linkages which can form hydrogen bonds with water 9,10 .…”
Section: Introductionmentioning
confidence: 99%